Helicobacter pylori Xanthine-Guanine-Hypoxanthine Phosphoribosyltransferase-A Putative Target for Drug Discovery against Gastrointestinal Tract Infections - Keough, Dianne T; Wun, Shun Jie; Baszczyňski, Ondřej; Eng, Wai Soon; Špaček, Petr; Panjikar, Santosh; Naesens, Lieve; Pohl, Radek; Rejman, Dominik; Hocková, Dana; Ferrero, Richard L; Guddat, Luke W (Journal of medicinal chemistry, 2021)
Helicobacter pylori (Hp) is a human pathogen that lives in the gastric mucosa of approximately 50% of the world's population causing gastritis, peptic ulcers, and gastric cancer. An increase in resistance to current drugs has sparked the search for new Hp drug targets and therapeutics. One target is the disruption of nucleic acid production, which can be achieved by impeding the synthesis of 6-oxopurine nucleoside monophosphates, the precursors of DNA and RNA. These metabolites are synthesized by Hp xanthine-guanine-hypoxanthine phosphoribosyltransferase (XGHPRT). Here, nucleoside phosphonates have been evaluated, which inhibit the activity of this enzyme with Ki values as low as 200 nM. The prodrugs of these compounds arrest the growth of Hp at a concentration of 50 μM in cell-based assays. The kinetic properties of HpXGHPRT have been determined together with its X-ray crystal structure in the absence and presence of 9-[(N-3-phosphonopropyl)-aminomethyl-9-deazahypoxanthine, providing a basis for new antibiotic development.
Keywords: kinetika; hypoxanthinfosforibosyltransferasa; sekvence aminokyselin; gastrointestinální nemoci; Anti-Bacterial Agents; Sequence Alignment; Helicobacter Infections; hypoxanthiny; Gastrointestinal Diseases; Pentosyltransferases; krystalografie rentgenová; pentosyltransferasy; Molecular Dynamics Simulation; Organophosphonates; infekce vyvolané Helicobacter pylori; Bacterial Proteins; Crystallography, X-Ray; Hypoxanthines; Prodrugs; vztahy mezi strukturou a aktivitou; Humans; Binding Sites; Amino Acid Sequence; prekurzory léčiv; antibakteriální látky; Kinetics; simulace molekulární dynamiky; Hypoxanthine Phosphoribosyltransferase; Helicobacter pylori; bakteriální proteiny; organofosfonáty; sekvenční seřazení; Structure-Activity Relationship; vazebná místa; lidé